-0.9x+1.93=-0.7x+6.73

Simple and best practice solution for -0.9x+1.93=-0.7x+6.73 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.9x+1.93=-0.7x+6.73 equation:


Simplifying
-0.9x + 1.93 = -0.7x + 6.73

Reorder the terms:
1.93 + -0.9x = -0.7x + 6.73

Reorder the terms:
1.93 + -0.9x = 6.73 + -0.7x

Solving
1.93 + -0.9x = 6.73 + -0.7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.7x' to each side of the equation.
1.93 + -0.9x + 0.7x = 6.73 + -0.7x + 0.7x

Combine like terms: -0.9x + 0.7x = -0.2x
1.93 + -0.2x = 6.73 + -0.7x + 0.7x

Combine like terms: -0.7x + 0.7x = 0.0
1.93 + -0.2x = 6.73 + 0.0
1.93 + -0.2x = 6.73

Add '-1.93' to each side of the equation.
1.93 + -1.93 + -0.2x = 6.73 + -1.93

Combine like terms: 1.93 + -1.93 = 0.00
0.00 + -0.2x = 6.73 + -1.93
-0.2x = 6.73 + -1.93

Combine like terms: 6.73 + -1.93 = 4.8
-0.2x = 4.8

Divide each side by '-0.2'.
x = -24

Simplifying
x = -24

See similar equations:

| x+2=2.3 | | (x+y)+(4y+x)=180 | | 3x^2=-42x | | 3x^2+7x=5x-7 | | 3x+y=.9 | | 2x+47=14 | | -7(y^2+18y+81)=-1372 | | 6f=-2f-8 | | 5x-2(x-5)=7 | | x+y=2.3 | | 2/5x^2-6=-4/5x | | 6x-12=4x-6 | | 4(8w+2)-5(4w+2)= | | 1/2x-12=4/3x+6 | | 7x+4=5x+3x-3 | | 4y-12+7y+16=180 | | x+3=5y+4 | | 900=-4x+967 | | 5x-10=5y | | 5/6=(y-6)/(y+1) | | x/3+10=24 | | 3f=-f-6 | | 3m+9m=10(11+3m)-9(6+2m) | | 5x-32=15x-88 | | 7(y-3)=4y-39 | | 2c+6/-2=18 | | 3x+5+4x-35=180 | | 2x-5=4x-11 | | (n+4)*7=66 | | 7x^2+46x=21 | | 2(x+2)+3(x+4)=39 | | 0.2x-3=.01x+5 |

Equations solver categories